An-Nida Theory According to the Perspective of Nahwu Sibawayh Thought - Vania Cahyaningtyas (Alfaz (Arabic Literatures for Academic Zealots), 2021)
The nahwu study cannot be separated from an important figure named Sibawayh. He is a scholarly figure who has been consensually recognized for this superiority and scientific genius, he is recommended as a reference for other scholars, especially when it comes to discussing knowledge about Arabic grammar in accordance with the rules. Although he was a native Persian who was not very good at conversing Arabic, he was a very influential expert on Arabic grammar. His effort entitled al-Kitab is the first recorded book of Arabic grammar. He has been recognized as one of the greateast linguists of all the time especially in the filed of nahwu among linguists in the world. Sibawayh contributed his thoughts about nahwu to several types in an-nida and munada according to his version. The research method used in writing this journal is a qualitative descriptive method, the writer describes munada and its types.